2016
DOI: 10.1515/biol-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic amines and hygienic quality of lucerne silage

Abstract: Open Life Sci. 2016; 11: 280-286 acetic acid (−46%), ammonium (−59%), ash (−13%) and fat (−24%). Populations of bacteria associated with lactic acid fermentation, moulds, yeasts, enterobacteria and total microorganisms count were also influenced. Both biological and chemical additives can be highly recommended for producing high-quality silages meeting hygienic requirements. In lucerne silage, the chemical preservative showed a stronger effect in achieving the health safety of silage compared to the biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Ash material was determined by weighing the material remaining after the burning of a fixed-weight sample at 550 °C and specified conditions. Nitrogenous substances were measured by the Kjeldal method (N × 6.25 coefficient) using the Kjeltec 2300 device (Foss Analytical, Hillerød, Denmark) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ash material was determined by weighing the material remaining after the burning of a fixed-weight sample at 550 °C and specified conditions. Nitrogenous substances were measured by the Kjeldal method (N × 6.25 coefficient) using the Kjeltec 2300 device (Foss Analytical, Hillerød, Denmark) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maize forage compaction ranged from 155 to 198 kg TS /m 3 (Table 2). Then, the mini-silo was hermetically sealed and placed in the dark to prevent exposure to light, at a temperature of 28 • C ± 1 • C. Each container was equipped with a safety valve for the removal of excessive gaseous products [28,29]. After the lapse of the incubation time of 90 days [29], the micro-silages were opened and samples of them were homogenized.…”
Section: Production Of Mixed Culture Silage-preparation Of Model Silagementioning
confidence: 99%
“…Numerous studies suggest that the occurrence of NH 3 and BAEs also exists in substantially well‐preserved silages (Mlejnkova et al, 2016; Scherer et al, 2015; Skladanka et al, 2017), but available studies merely focused on the effect of different additives on the concentrations of NH 3 and BAEs, whilst information on functional micro‐organisms and active mechanisms remain mostly undescribed. Our previous findings showed that sucrose addition could effectively improve the fermentation quality of alfalfa silage (Li, et al, 2020; Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%